POSITIVE POLITENESS STRATEGIES USED BY THE CHARACTERS IN “TURNING RED” MOVIE - Septaria, Herti Nurizka; Ambalegin, Ambalegin (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research purposed to discover the positive politeness strategy and used the theory from Brown and Levinson (1987) of positive politeness. And for the data source, this research took a movie titled “Turning Red”. This study used the descriptive qualitative method from (Creswell, 2013). In collecting and analyzing the data this research applied the theory from (Sudaryanto, 2015). The final result of this study discovered 21 data of positive politeness done by the characters. Offer,promise, occurred 5 times as the most strategy used. And exaggerate occurred 2 times. Use in-group identity markers that appeared 2 times. Seek agreement appeared 1 time. Presuppose appeared 1 time. Assert or presuppose speaker‘s knowledge of and concern for interlocutor‘s wants appeared 2 times. Include both speaker and interlocutor in the activity with 4 times occurrence. Assume or assert reciprocity occurred 3 times, and give a gift occurred 1 time. The results of this study contribute to knowledge of various positive politeness strategies that exist in